MODEL CALCULATIONS OF THERMODYNAMIC PROPERTIES OF LIQUID ALLOYS IN Cu–Lu AND Fe–Lu SYSTEMS: UDC 541.11 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Model calculations of the wide range of thermodynamic properties of binary liquid alloys of iron with lutetium and cuprum with lutetium were carried out using our previously obtained data on partial and integral enthalpies of mixing in these systems. The ideal associated solution model was used to obtain the thermodynamic values. Obtained via ideal associated solution model values of Gibbs energies and excess Gibbs energies of binary liquid alloys of lutetium with iron and cuprum can be used to provide calculations of thermodynamic properties and phase diagrams of multicomponent Fe- (Cu-) and Lu-contained alloys. It is shown that ideal associated solution model is the effective instrument of modelling of thermodynamic properties of the alloys for which noticeable negative deviations of ideal solution behavior are observed due to considerable component interaction in liquid state. Liquid alloys of the investigated systems are characterized by the existence of the short range order of the type of chemical compound. Rather high values of mole fractions of associates obtained during IASM calculations lead to this conclusion. Despite the fact that each phase diagram of investigated systems is characterized by its own set of compounds the curves of integral ebthalpies of mixing in these systems are characterized by similar concentration dependences and can be reproduced using the same set of associates (MeLu and Me2Lu). This fact may indicate a similar character of component interaction in liquid alloys of Cu–Lu and Fe–Lu systems.
Keywords: iron; cuprum; lutetium; thermodynamic properties of liquid alloys; ideal associated solution model